Casual Genetic Variants in Stillbirth. Issue 2 (February 2021) - Stanley, Kate E.; Giordano, Jessica; Thorsten, Vanessa; Buchovecky, Christie; Thomas, Amanda; Ganapathi, Mythily; Liao, Jun; Dharmadhikari, Avinash V.; Revah-Politi, Anya; Ernst, Michelle; Lippa, Natalie; Holmes, Halie; et al.
Abstract : (Abstracted from N Engl J Med 2020;383:1107–1116) Stillbirth is defined as fetal death in utero at ≥20 weeks' gestation. It makes up 60% of all perinatal deaths, but the cause remains unknown in 25% to 60% of cases.